miRNA-mediated feedback inhibition of JAK/STAT morphogen signalling establishes a cell fate threshold. - Yoon, W.H.; Meinhardt, H.; Montell, D.J. (Nature Cell Biology, 2011)
Patterns of cell fates generated by morphogens are critically important for normal development; however, the mechanisms by which graded morphogen signals are converted into all-or-none cell fate responses are incompletely understood. In the Drosophila ovary, high and sustained levels of the secreted morphogen Unpaired (Upd) specify the migratory border-cell population by activating the signal transducer and activator of transcription (STAT). A lower or transient level of STAT activity specifies a non-migratory population of follicle cells. Here we identify miR-279 as a component of a feedback pathway that further dampens the response in cells with low levels of JAK/STAT activity. miR-279 directly repressed STAT, and loss of miR-279 mimicked STAT gain-of-function or loss of Apontic (Apt), a known feedback inhibitor of STAT. Apt was essential for miR-279 expression in non-migratory follicle cells, whereas another STAT target, Ken and Barbie (Ken), downregulated miR-279 in border cells. Mathematical modelling and simulations of this regulatory circuit including miR-279, Apt and Ken supported key roles for miR-279 and Apt in generating threshold responses to the Upd gradient.